Develop an Android-Based Learning Media Integrated with a Scientific Approach to the Colligative Solution's Nature - Yohan Aji Pratama; Zainuddin Muchtar; Ayi Darmana (BIRCU, 2021)
This study aimed to develop an Android-based learning media integrated with a scientific approach to the colligative solution's nature. This study uses the Research and Development (R & D) method with the ADDIE model development stages. The population of the study was all students of class XII SMA using the 2013 curriculum. The sample was class XII SMA Swasta Al - Azhar Medan. The validation of learning media based on Android integrated scientific approach by material experts and media experts obtained a feasibility score of 4.4 and 4.8, respectively. In contrast, the feasibility score by two chemistry teachers received an average value of 4.7. The validation of Android-based learning media integrated with the scientific approach shows that the average score is 4.6, which means that the learning media used has very feasible criteria. Android-based learning media products integrated with the scientific approach were tested on 26 students of class XII at Al-Azhar Medan Private High School. The results showed that the learning media that had been compiled could be used as learning media for the colligative solution's nature.